2020
DOI: 10.3892/mmr.2020.10987
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA MALAT1 regulates cholesterol accumulation in ox‑LDL‑induced macrophages via the microRNA‑17‑5p/ABCA1 axis

Abstract: atherosclerosis (aS), a major cause of cardiovascular disease, has developed into a serious challenge to the health system. The long non-coding rna (lncrna) metastasis associated lung adenocarcinoma transcript 1 (MalaT1) is associated with the pathogenesis of aS. However, whether MalaT1 can affect cholesterol accumulation in macrophages during aS progression, and the potential molecular mechanism involved in this progression have not been elucidated. in the present study, the mrna expression level of MalaT1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Earlier report Yan et al [36] suggested that MALAT1 promotes hepatic steatosis by increased stability of SREBP-1c protein. Liu et al [37] presented that it is involved in regulating cholesterol accumulation in ox-LDL-induced macrophages via microRNA-17-5p/ABCA1 axis. The study analysed MALAT1, and TUG1 expression in AT in the obesity context showed no differences between obese and normal women, but MALAT1 mRNA level in SAT was positively correlated with SREBP-1c, PPARγ, and their targets; FAS and ACACA, as well as with VAT mRNA levels of PGC1α [38].…”
Section: Validation Of Rna-seq Resultsmentioning
confidence: 99%
“…Earlier report Yan et al [36] suggested that MALAT1 promotes hepatic steatosis by increased stability of SREBP-1c protein. Liu et al [37] presented that it is involved in regulating cholesterol accumulation in ox-LDL-induced macrophages via microRNA-17-5p/ABCA1 axis. The study analysed MALAT1, and TUG1 expression in AT in the obesity context showed no differences between obese and normal women, but MALAT1 mRNA level in SAT was positively correlated with SREBP-1c, PPARγ, and their targets; FAS and ACACA, as well as with VAT mRNA levels of PGC1α [38].…”
Section: Validation Of Rna-seq Resultsmentioning
confidence: 99%
“…Serum insulin level was determined by ELISA using an ultra-sensitive mouse insulin kit (Crystal Chem, USA) ( Ding et al., 2016 ). Serum levels of total cholesterol, triglycerides, LDL-C, HDL-C, and free fatty acids (FFA) levels were assayed using the calorimetric kits from Nanjing Jiancheng Bioengineering Institute (Nanjing, China) ( Jiang et al., 2016 ; Wang et al., 2019 ; Liu et al., 2020 ). Liver TG was analyzed using Tissue triglyceride assay kit (Applygen, Beijing, China) ( Wang C. et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (lncRNA MALAT1) is recognized as a biomarker in various cancers, and recent studies indicate that it is also involved in the pathogenesis of atherosclerosis. [7][8][9][10] Mechanically, lncRNA MALAT1 silencing attenuates oxidized low-density lipoprotein (ox-LDL)-induced endothelial inflammation and protects the endothelium from oxidative stress, further affecting the progression of atherosclerosis. 7 Additionally, another study indicates that lncRNA MALAT1 affects lipid metabolism disorder and is associated with inflammation response as well as the pathological progression of atherosclerosis via regulating ox-LDL-related macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…7 Additionally, another study indicates that lncRNA MALAT1 affects lipid metabolism disorder and is associated with inflammation response as well as the pathological progression of atherosclerosis via regulating ox-LDL-related macrophages. 8 Furthermore, lncRNA MALAT1 is reported to regulate cardiac inflammation and promote acute myocardial infarction via interaction of microRNA-125b (miR-125b), and miR-125b serves as a pathogenic mediator in multiple vascular diseases. [11][12][13] For example, miR-125b attenuates endothelin-1 expression, suppresses vascular endothelial-cadherin mRNA translation, and reduces endothelial permeability, involving the development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%